La « révolution » de 1964 et la commémoration de l’indépendance brésilienne - Maud Chirio (Caravelle)
This paper aims at exploring what links nationalism and Historia Patria, to the military who lead Brazilian State from 1964 to 1985. For that matter, it studies the celebrations of Independence Day (commemoration of September 7th, 1822), which became a national holiday in 1826. Since they lack of inventiveness in the remembrance field, the generals took over the already existing rituals and symbols. They inserted their « democratic and redemptive Revolution » (so was officially called their seizure of power) into the Nation’s history, whose destiny they would fulfil, by bringing it peace, power and greatness.